"GST and Its Way Forward" - K K Sri Rama Chandra Murthy (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
GST is a value added tax. France is the First Country introduced this GST followed by numerous Countries. In India GST was first recommended by the Kelkar Task Force on implementation of Fiscal Reforms and Budget Management Act, 2004. Notwithstanding that, the first Discussion paper on Goods and Services Tax in India was presented by the Empowered Committee of State Finance Ministers dated 10th November 2009. More competitive business environment, uniform tax rates across states, better interstate trade, no confusion with regard to economic activity, no cascading effect i.e., no taxes on taxes, ease on money fronts, and widening tax base, etc., are the interesting features of GST. Increased monopoly of Central Government, States lose a share of revenue, and Burden on tax payers, etc., are the frequently raised criticisms against GST. The other criticisms raised against GST are Legislative powers relating to Tax on Goods Services captured by the GST Implementation Committee and the Central Government. Moreover, GST dues, payment of compensation stopping or delay in payment of compensation ultimately forcing the states to beg the Central Government for the same. The objective of this article is to verify the criticisms levelled against the GST. Exemptions to Charitable and religious activities, Healthcare sector and Legal services are discussed in this Article. In this article doctrinal and analytical method of research is adopted.